Doing Cultural History : Insights, Innovations, Impulses - Mengler, Judith; Müller-Bongard, Kristina (Bielefeld : Transcript-Verlag, 2018)
"Doing Cultural History" collects papers on a variety of topics. The issues addressed span from the 12th to the 21st century and include the communication of peace in written and pictorial sources, narrative structures in legal texts, masculinity and violence, and new research into Scottish medieval history as well as a comparison of religious theme parks and the perception of sorcery and false saintliness in early modern Spain.
Frontmatter -- Editorial -- Content -- Preface / Rogge, Jörg -- Introduction / Mengler, Judith / Müller-Bongard, Kristina -- A Black and White Peace. On the Possibility of Peace within the Dichotomies of Arthurian Literature / Däumer, Matthias -- Writing war -- communicating peace? The peace treaty of Edinburgh- Northampton of 1328 / Hachgenei, Davina -- Peace on Paper Illustrated in Pictures. The visual representation of peace treaties in Early Modern Europe / Müller-Bongard, Kristina -- Narrative Structures in Legal Texts An Introduction to the Panel / Backerra, Charlotte / Sarti, Cathleen / Schlarb, Damien B. -- Narrative Elements in Deposition Documents / Sarti, Cathleen -- Sentimental Contracts. The Affective Narrative Structure of Puritan Covenant Theology in Jonathan Winthrop's A Model of Christian Charity / Schlarb, Damien B. -- Narrative Elements in Treaties of Peace and Alliance / Backerra, Charlotte -- The Jerusalem Experience Comparing Theme Park Versions of the Holy Land / Molter, Céline -- Searching for other spaces, or: How useful is Foucault's concept of heterotopias as a method for historical research effectively? / Frohnapfel-Leis, Monika -- Man as Victims. Speaking and laughing about violence against men / Schuh, Dominik -- Courageous surgeons, enduring patients The performance of masculinity in medieval military medicine (14th-15th century) / Mengler, Judith -- Clash of Civilisations in Medieval Scotland or Can Culture Explain Conflict? / Berlandi, Matthias -- At the forefront of resistance to England? Melrose Abbey and the Scottish Wars of Independence / Weil, Sebastian -- Between Love and Social Advancement. The Marriage Arrangements of the Late Medieval Maxwells of Caerlaverock Castle / Noll, Julia -- Contributors -- Backmatter.
In English.
Online resource; title from PDF title page (publisher's Web site, viewed 24. Sep 2018).
eBooks on EBSCOhost
Keywords: Civilization -- Historiography; Civilisation -- Historiographie; HISTORY / Social History; Civilization -- Historiography; Essay; Gender Studies; History; Media; Perception; Electronic books; Electronic books